Focal Necrosis and Disturbed Myelination in the White Matter of Newborn Infants: A Tale of Too Much or Too Little Oxygen - Wellmann, Sven; Bührer, Christoph; Schmitz, Thomas (Frontiers in Pediatrics, 2015)
White matter disease in preterm infants comes along with focal destructions or with diffuse myelination disturbance. Recent experimental work with transgenic mice paves the way for a unifying molecular model for both types of brain injury, placing oxygen sensing by oligodendrocyte precursor cells at the center stage. Mice genetically altered to mimic high local oxygen tension in oligodendroglia lineage cells (via deletion of hypoxia-inducible factor, HIF) develop white matter disease resembling cystic periventricular leukomalacia (cPVL) within the first 7 days of life. Mice in which local hypoxia is mimicked in oligodendroglial cells (via genetic inhibition of HIF decay) display arrested oligodendrocyte precursor cell maturation and subsequent hypomyelination, reminiscent of the diffuse white matter disease (dWMD) observed in preterm infants and infants with congenital heart disease. These recent experimental findings on oxygen sensing and myelination are awaiting integration into a clinical framework. Gene regulation in response to hyperoxia or hypoxia, rather than oxidative stress, may be an important mechanism underlying neonatal white matter disease.